Telepresent Agency: Remote Participation in Hybrid Language Classrooms via a Telepresence Robot - Jakonen Teppo; Jauni Heidi (Springer, 2023)
Videoconferencing technologies have become increasingly common in different sectors of life as a means to enable real-time interaction between people who are located in different places. In this chapter, we explore interactional data from synchronous hybrid university-level foreign language classrooms in which one student participates via a telepresence robot, a remote-controlled videoconferencing tool. In contrast to many other forms of video-mediated interaction, the user of a telepresence robot can move the robot and thereby (re-)orient to the space, the other participants and material objects that might be outside his immediate video screen. We employ an ethnomethodological and conversation analytic (EMCA) perspective to explore Barad’s (Quantum physics and the entanglement of matter and meaning. Durham: Duke University Press: 2007) notion of agency as a distributed phenomenon that emerges from assemblages of humans and materials. We demonstrate the complex nature of telepresent agency by investigating where agential cuts lie in three short episodes that involve mediated perception, touch and movement. Based on the analyses, we discuss how the telepresence technology configures learning environments by making new kinds of competences and forms of adaptation relevant for teachers and students.
New Materialist Explorations into Language Education